1998
DOI: 10.1177/003072709802700110
|View full text |Cite
|
Sign up to set email alerts
|

Communication of Improved Farm Practices to Rural Women Farmers in Benue State, Nigeria

Abstract: A study was conducted to investigate the communication process through which the extension workers of Benue Agricultural and Rural Development Authority (BNARDA) disseminate improved farm practices to rural women farmers. A total of 250 women farmers who were in contact with the extension services were randomly selected and interviewed. The results showed that 90% of them recognized personal contacts, group meetings of farmers, and method-and-result demonstration sites as channels through which they communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…The factors include household preferences, resource endowments, market incentives, biophysical factors and risk and uncertainty. Furthermore, studies have shown that the age of the household head, education level, gender, household wealth, household size, farmland size and access to agricultural inputs all influence farmers’ adoption of agroforestry technologies (Omuregbee, 1998; Ndayambaje, 2013). In a study of patterns of tree adoption on farms in Ethiopia, Iiyama et al (2017) found that favorable climatic conditions and institutional arrangements to control free grazing influence adoption.…”
Section: Introductionmentioning
confidence: 99%
“…The factors include household preferences, resource endowments, market incentives, biophysical factors and risk and uncertainty. Furthermore, studies have shown that the age of the household head, education level, gender, household wealth, household size, farmland size and access to agricultural inputs all influence farmers’ adoption of agroforestry technologies (Omuregbee, 1998; Ndayambaje, 2013). In a study of patterns of tree adoption on farms in Ethiopia, Iiyama et al (2017) found that favorable climatic conditions and institutional arrangements to control free grazing influence adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies (Masangano, 1996;Omuregbee, 1998) have identified some of the farmers' characteristics that may influence adoption of agroforestry technologies. These include the age, gender, and education level of the household head; wealth, family size, group membership, and farm resources (such as farm size, land tenure, credit or other inputs, and availability of labor).…”
Section: Introductionmentioning
confidence: 99%
“…, Ayinde et al, (2010), Namwata et al, (2010), Odoemenem and Obinne (2010), Matata et al, (2010), Boahene et al, (1999), and Omoregbee (1998).…”
Section: Socio Economic Characteristics Of the Cotton Farmers In The mentioning
confidence: 99%